Patient‐reported outcomes, postoperative pain and pain relief after day‐case surgery ( POPPY ): acute pain and recovery during the first 7 days - Matthew Everson; Martha Belete; Adam Brayne; Harriet Daykin; William M. Hare; Anna Ratcliffe; Lexy Sorrell; Mark Rockett (Anaesthesia, 2026)
Summary Introduction The majority of surgical cases in the UK occur in a day‐case setting. Published short‐term follow‐up studies after day‐case surgery are lacking and patterns of recovery including pain and patient reported outcome measures, are largely unknown. Methods Data from the Patient‐reported Outcomes, Postoperative Pain and pain relief after daY case surgery (POPPY) study, a national, prospective, observational study exploring outcomes following day‐case surgery in the UK, were used to explore acute recovery over the first 7 postoperative days. Baseline data were captured on the day of surgery alongside pain severity, functional scores and quality of recovery‐15 scores on postoperative days 1, 3 and 7. A poor pain outcome was defined as a pain severity score of > 4/10 and a poor functional outcome was defined as any functional impairment due to pain on days 1, 3 and 7. Results Of the 7839 patients initially recruited, 7331 responded on day 7. Pain severity scores decreased over the first postoperative week and yet pain impaired function in 1279/4854 (26.3%) patients at day 7. In the first 7 days, 1458/4348 (33.5%) of patients had a poor pain outcome. Associated variables included: treatment for anxiety or depression; baseline chronic pain; frailty; greater surgical magnitude; and type of surgery (head and neck surgery). Increasing age was associated with reduced probability of poor pain outcomes. Poor functional outcomes were associated with: surgical magnitude; type of surgery (orthopaedic surgery); chronic pain; and frailty. Opioid naivety was associated with a reduced odds ratio of both poor pain and functional outcomes. Discussion These findings suggest that by postoperative day 7, recovery from day‐case surgery is incomplete for many patients. We identified characteristics associated with poor pain and functional outcomes that could be used to improve peri‐operative pathways, in particular highlighting patients who may benefit from enhanced preparation and closer follow up.